مفهوم الحضارة ومقوماتها بين سيد قطب ومالك بن نبي: دراسة مقارنة في الرؤية والمنهج والتطبيق : The Concept of Civilization and Its Components in the Thoughts of Sayyid Qutb and Malek Bennabi: A Comparative Study of Their Perspectives, Methodologies, and Practical Applications - Alisakun, Shakira; Berghout, Abdelaziz (Journal of Al-Tamaddun, 2025)
The quest for revival, civilizational renewal, and the establishment of a robust civilization has been a central theme for the nation over the past decades. Many scholars and intellectuals have enriched this dialogue, offering diverse perspectives. Among the most impactful contributors to revivalist thought are Sayyid Qutb and Malek Bennabi, each proposing unique approaches. This study explores Qutb’s and Bennabi’s respective visions for the concept and components of civilization. It further analyzes the intellectual, methodological, and practical similarities and distinctions between their approaches to theory-building. Using an analytical-deductive approach, the study examines each thinker’s perspective on civilization and employs a comparative framework to highlight areas of convergence and divergence. Findings show that both thinkers reject adopting ready-made models, advocating instead for an integration of moral and material dimensions as foundational to civilization. However, their intellectual emphases differ significantly: Qutb’s approach is doctrinally focused, while Bennabi’s is grounded in social structures. Methodologically, Qutb’s perspective has a literary style, whereas Bennabi’s is scientific. Practically, Qutb favors a revolutionary approach, while Bennabi advocates for a dynamic, interactive model that may be more feasible to implement.